Lifestyle Determination of Blood Glucose in Type 2 Diabetes Mellitus Outpatients - Septiannisa, Rifka; Prameswari, Fajria Saliha Puspita; Fauza, Ahdiyatul; Fitrianingsih, Asti Dewi Rahayu (Ikatan Sarjana Gizi Indonesia (ISAGI), 2026)
This study aimed to examine the correlation between the frequency of ultra-processed food (UPF) intake, blood pressure, and physical activity in outpatients with type 2 diabetes mellitus (T2DM) at RSAU dr. M. Salamun. A cross-sectional research design was employed. The study population comprised outpatients attending the Interne Polyclinic at RSAU dr. M. Salamun, and a total of 50 participants were selected using a total sampling technique. Data analysis was conducted using the Shapiro-Wilk test for normality and the Spearman Rho test for correlation. The results indicated a significant correlation between blood pressure and physical activity with fasting blood glucose (FBG) levels (p < 0.05). These findings suggest that elevated blood pressure and low levels of physical activity negatively impact glycemic control. Therefore, lifestyle interventions focusing on blood pressure management and increased physical activity may contribute to improved blood glucose regulation in individuals with T2DM.